Enhanced Anticancer Potential of Pd(II)-Thiosemicarbazone Complexes: Selectivity, Mechanisms, and 3D Models - Mauro A. Lima; Tamara Teixeira; Dario B. Fortaleza; George B. S. Pereira; Amos O. Akinyemi; Carlos André Ferreira Moraes; Moacir R. Forim; Alzir A. Batista; Jocely L. Dutra; João H. Araujo-Neto; Javier A. Ellena; Fillipe V. Rocha (Pharmaceutics, 2025)
Background/Objectives: Cancer remains a major global health challenge, driving the search for novel chemotherapeutic agents. This study aimed to evaluate the structural and biological properties of a series of Pd(II) complexes containing triphenylphosphine and thiosemicarbazone ligands, in order to assess their potential as anticancer agents. Methods: Six Pd(II) complexes with the general formula [PdCl(PPh3)(TSC)] were synthesized and fully characterized by NMR (1H, 1³C, ³1P), FTIR, mass spectrometry, and X-ray diffraction. Their cytotoxic effects were investigated through in vitro assays using 2D and 3D cancer cell models, including clonogenic, wound healing, cell cycle, and apoptosis assays via flow cytometry. Results: Complexes from the B family demonstrated significantly higher cytotoxicity than those from the C family, particularly against ovarian (IC50 < 1 µM) and breast (IC50~2 µM) cancer cell lines. These compounds exhibited superior potency and selectivity compared to cisplatin, with high selectivity indices toward non-tumor cells. Mechanistic studies revealed both cytotoxic and cytostatic effects depending on structural variations, with apoptosis identified as the primary mechanism of cell death. PdB1, in particular, induced a marked increase in late apoptotic populations and maintained its cytotoxic activity in 3D spheroid models by promoting disintegration, loss of cell adhesion, and nuclear fragmentation. Conclusions: The findings underscore the therapeutic promise of Pd(II) complexes, especially PdB1, as potent and selective antineoplastic agents capable of acting effectively in complex tumor environments and potentially overcoming chemoresistance.